2020
DOI: 10.3389/fmicb.2020.01287
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Signals Alter in vitro Soil Virus Abundance and Bacterial Community Composition

Abstract: Cell-density dependent quorum sensing (QS) is fundamental for many coordinated behaviors among bacteria. Most recently several studies have revealed a role for bacterial QS communication in bacteriophage (phage) reproductive decisions. However, QS based phage-host interactions remain largely unknown, with the mechanistic details revealed for only a few phage-host pairs and a dearth of information available at the microbial community level. Here we report on the specific action of eight different individual QS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…The abundance of lysogens can be inversely correlated to primary productivity, since low nutrient conditions may reduce host densities and compromise further viral progeny (4). In agreement with this supposition, spontaneous induction of prophages has been observed under high-cell-density conditions (53,54), whereas treatment of soil and groundwater samples with AHLs significantly increased viral abundance (55,56). These findings strongly emphasize that population density may be a critical determinant of phage-host interactions; phages may exploit diverse QS communication systems to link host cell density and phage decisions, providing novel insights into the regulatory mechanisms implicated in the developmental fate of phages.…”
Section: Quorum Signaling and Phage Developmentsupporting
confidence: 63%
“…The abundance of lysogens can be inversely correlated to primary productivity, since low nutrient conditions may reduce host densities and compromise further viral progeny (4). In agreement with this supposition, spontaneous induction of prophages has been observed under high-cell-density conditions (53,54), whereas treatment of soil and groundwater samples with AHLs significantly increased viral abundance (55,56). These findings strongly emphasize that population density may be a critical determinant of phage-host interactions; phages may exploit diverse QS communication systems to link host cell density and phage decisions, providing novel insights into the regulatory mechanisms implicated in the developmental fate of phages.…”
Section: Quorum Signaling and Phage Developmentsupporting
confidence: 63%
“…On the contrary, native bacteria can protect themselves against colonization by sacrificing a part of the population and inducing their prophages’ lytic cycle [ 101 ]. Lysogenic bacteria can use their prophage weapon effectively, as observed in an in vitro experiment recently, where a lysogenic-lytic switch of bacteriophages to QS autoinducers strongly influenced the viral and bacterial abundance and diversity in soil communities [ 112 ].…”
Section: Xanthomonas -Host Plant and Bacteriophage-host Bacterium Interactions And Their Possible Influence On Bacteriophage-basmentioning
confidence: 99%
“…A number of studies have shown that plant responses to certain AHL molecules are specific depending on the length of the acyl moiety [20][21][22]. Not only do AHL molecules affect plant responses, but a study by Liang et al [23] showed that a variety of AHLs can affect the bacterial community. In this study, we hypothesize that treatment of AHL could be potentially used to alleviate the problems that occur during monocropping by shifting the soil microbiome in addition to their plant growth promoting activity.…”
Section: Introductionmentioning
confidence: 99%